Osteosynthesis and radial head arthroplasty achieve comparable and favorable results in terrible triad injury: a systematic review using propensity score matching - John J Heifner; Asdrubal E Rivera Dones; A Laurie Wells; Christopher W Reb; Deana M Mercer (Journal of Orthopaedics, Trauma and Rehabilitation)
The terrible triad literature reports data across wide ranges of patients ages and the treatment allocation for the radial head is commonly based on fracture severity. These observations raise the question of selection bias which can hinder comparative efficacy. Propensity score matching analysis may provide better control of patient variables and treatment allocation. We convey two conclusions from this analysis. Firstly, clinical outcome metrices were favorable for both radial head arthroplasty and open reduction internal fixation following terrible triad injury. This finding supports the recent literature which describe satisfactory outcomes for acute surgical management of these injuries. Secondly, the analysis suggests that revision rates may be lower for both treatment options than previously reported in the literature.